Effective collaboration : developing the skills you need to maximize results. - O'Leary, Zina (O'Reilly Media, Inc., 2023)
Today's competitive work environment means that insular approaches to work are no longer sufficient. There is a need to work together in ways that give an edge in navigating uncertainty, generating innovative ideas, and embracing new ways of working. When we integrate diverse perspectives, we gain the ability to push past the status quo and become the innovators organizations need. This course will help participants develop interpersonal skills, improve work base outcomes, and embed leadership skills that can facilitate quicker turnaround times, organizational scalability, lower costs, a flexible and creative culture. Join Zina O'Leary on this online course as she helps you develop key collaboration skills that will be applicable throughout your career. What you'll learn and how you can apply it Work with new perspectives in order to generate new ideas and reach better solutions Lead more effectively from the front, the side, and behind Listen in a more active and non-defensive way Build trusting, safe environments Facilitate and contribute to brainstorming Better move ideas into action Engage in conflict resolution Become more transparent and accountability This course is for you because... You're an individual contributor interested in collaborating and more effectively within an organization. You manage a team and you need to be able to facilitate collaborative teams that work well together. You're a leader within your organization and you want to increase trust, credibility, and effectiveness across the organization. You want to be part of creating an enduring collaborative culture that fosters sustainable success.